Vegamales_esurge - Markussen, Stine; Herfindal, Ivar; Loison, Anne; Solberg, Erling; Haanes, Hallvard; Røed, Knut; Heim, Morten; Sæther, Bernt-Erik (Dryad Digital Repository, 2018)
Input file for E-SURGE for male moose at Vega, Norway, 1984-2012.